ULMINJUM CHUBUTENSE N. SP. (LAURACEAE), LEÑO PERMINERALIZADO DEL TERCIARIO INFERIOR DE BAHIA SOLANO, CHUBUT, ARGENTINA (Ameghiniana, 2014)
Petrified wood of a new species of Ulminium has been described from Lower Tertiary sediments of Bahía Solano. This species shows a unique combination of features: -diffuse porosity. solitary pores, inradial multiple pores of 2-7 elements and clustered pores, round or oval numerous (14/mm2), small and short, simple perforation plate, intervascular alternate lo opposite pitting, tylosis, heterogeneous and heterocellular radii, axial parenchyma vasicentric and axial parenchyma bands more Ihan Ihree cells wide. The comparison with members of Lauraceae shows that Ulminium chubutense is different from other known fossil species and is similar to the extant genus Nectandra .